2015
DOI: 10.1016/j.apsb.2015.02.003
|View full text |Cite
|
Sign up to set email alerts
|

Kallistatin, a new and reliable biomarker for the diagnosis of liver cirrhosis

Abstract: Kallistatin, which protects organs and cells against inflammation, fibrosis and oxidative stress, is mainly synthesized and secreted in liver. However, its relationship to human liver disease remains unclear. The purpose of this study was to explore the relationship between serum kallistatin and clinical evidence of both cirrhosis and hepatocellular carcinoma (HCC), and to determine if serum kallistatin levels could be used as a diagnostic indicator of hepatic health status, especially human liver cirrhosis (L… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
28
3
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(44 citation statements)
references
References 39 publications
10
28
3
2
Order By: Relevance
“…Also, they declared that SERPINA4 was highly expressed in the normal human tissue, but its expression decreased in cases with liver fibrosis. Furthermore, Chao et al This finding is in a good agreement with that obtained by Cheng et al [17] who found that kallistatin level reduced significantly in the serum of early liver fibrosis patients; however, there was a marked reduction in kallistatin level of cirrhotic patients.…”
Section: ]supporting
confidence: 82%
“…Also, they declared that SERPINA4 was highly expressed in the normal human tissue, but its expression decreased in cases with liver fibrosis. Furthermore, Chao et al This finding is in a good agreement with that obtained by Cheng et al [17] who found that kallistatin level reduced significantly in the serum of early liver fibrosis patients; however, there was a marked reduction in kallistatin level of cirrhotic patients.…”
Section: ]supporting
confidence: 82%
“…Human kallistatin levels are significantly decreased in liver cirrhosis, sepsis, and inflammatory bowel disease, suggesting kallistatin is consumed in these diseases [5, 24, 25]. We previously demonstrated that patients with severe pneumonia had decreased plasma levels of kallistatin [20].…”
Section: Discussionmentioning
confidence: 99%
“…Plasma kallistatin levels are significantly reduced in patients with prostate and colon cancer [28]. Recent studies highlight the potential of kallistatin as a biomarker for the diagnosis of liver cirrhosis and an independent prognostic indicator for colorectal cancer [106, 107]. Therefore, it is possible that kallistatin’s role as a biomarker can also be applied to diverse human cancers.…”
Section: Discussionmentioning
confidence: 99%